2014
DOI: 10.1002/elps.201300411
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in capillary electrophoretic migration techniques for pharmaceutical analysis

Abstract: Since the introduction about 30 years ago, CE techniques have gained a significant impact in pharmaceutical analysis. The present review covers recent advances and applications of CE for the analysis of pharmaceuticals. Both small molecules and biomolecules such as proteins are considered. The applications range from the determination of drug-related substances to the analysis of counterions and the determination of physicochemical parameters. Furthermore, general considerations of CE methods in pharmaceutical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
68
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 214 publications
(277 reference statements)
0
68
0
Order By: Relevance
“…A recent review by Deeb et al (2014) showed that the number of advances and applications to pharmaceutical analysis by CE is continuously increasing. Method development strategies, validation and instrument qualification can be used for overcoming challenges related to low sensitivity or precision (Deeb et al 2014), but these are not the main concerns in the process analyses considered here.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent review by Deeb et al (2014) showed that the number of advances and applications to pharmaceutical analysis by CE is continuously increasing. Method development strategies, validation and instrument qualification can be used for overcoming challenges related to low sensitivity or precision (Deeb et al 2014), but these are not the main concerns in the process analyses considered here.…”
Section: Introductionmentioning
confidence: 99%
“…Method development strategies, validation and instrument qualification can be used for overcoming challenges related to low sensitivity or precision (Deeb et al 2014), but these are not the main concerns in the process analyses considered here. Requirements for monitoring high-volume bulk processes differ from those for monitoring highly regulated, sophisticated processes, such as pharmaceutical chemicals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CE is an appropriate technique for analyzing pharmaceuticals and biopharmaceuticals [1][2][3][4][5] for which using small volume samples is advantageous. There are numbers of benefits involved in handling small sample volume in CE, among which using less material, generating less waste, and applying high concentrations of valuable samples, which are all very important from an economic perspective stand out [6,7].…”
mentioning
confidence: 99%